PERBANDINGAN PENGATURAN SANKSI PIDANA TERHADAP PELAKU PEDOFILIA DALAM HUKUM POSITIF INDONESIA DAN HUKUM ISLAM - Vidya Sanaya; Erdianto Effendi; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This study examines the punishment for pedophiles from a perspective Indonesian positive law and Islamic law. This paper focuses on the fall penalties for pedophiles, who then compare penalties for pedophiles based on both sources of law, namely positive law and Islamic criminal law.This type of research can be classified in the type of normative research. In this study, the focus is to examine the comparison of punishments from the two sources of law, namely Indone-sian positive law and Islamic law. The data source used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection tech-nique in this research is the literature review method, after the data is collected then it is ana-lyzed to draw conclusions.The results of the study were analyzed using a comparison of the two legal concepts. From the two sources of law, there are differences in the punishment of the two concepts of legal sources. In Indonesia's positive law, penalties for pedophiles are the main punishment in the form of imprisonment and deda as well as additional penalties in the form of announcing the identity of the perpetrator, rehabilitation, chemical castration and the installation of electronic detection devices. In Islamic law, the punishment for a pedophile if what the pedophile commits is an act of adultery, the punishment is punishment for adultery (had az zina), which is stoning to death if it is muḥṣān (married) or whipping a hundred times if not muḥṣān and exiled for a year. If what the pedophile does is liwath (homosexual), then the punishment is the death penalty, not something else. If what is done is sexual harassment (at taharusy al jinsi) which does not lead to adultery or homosexuality, the punishment is ta'zir.Keywords : Punishment – Pedophilia - Indonesian positive law and Islamic law.